Analisis Peran Kepala Sekolah Dalam Meningkatkan Kemampuan Guru Dalam Penggunaan Penilaian Berbasis E-Rapor - Melkianus Panda Huki; Anam Sutopo; Sofyan Anif (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The implementation of e-Report card-based learning assessment requires teachers to strengthen their competence, particularly in information technology mastery, making the role of the school principal strategic. This study aims to analyze and describe the school principal's strategies in improving teachers' abilities to implement e-Report-based learning outcome assessment, as well as to identify the supporting and inhibiting factors in its implementation at SD Inpres Mahambala. This study uses a qualitative approach with a descriptive research type. Data were collected through interviews, observations, and documentation studies with the main data sources including the principal and six homeroom teachers selected purposively. Data analysis was conducted using the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the principal plays an active role through coaching strategies such as training, workshops, internal discussions, technical assistance, and facilitation of teacher ICT competency development. Although teachers' abilities in using e-Rapor still vary, the principal's policies and continuous support contributed to improving teachers' competencies. The implications of this study emphasize the importance of school principal leadership in supporting effective and accountable digital transformation of educational assessment.